Characterization and expression studies on Grb10b gene in zebrafish - Wong, Nelly Pei Pei (Universiti Malaysia Sarawak, UNIMAS, 2010)
Grb10 gene in mammals encodes for the growth factor receptor-bound protein 10 which belongs to a family of adapter protein that was found to interact with a number of receptor tyrosine kinases and signaling molecules. Two copies of Grb10 genes were identified in Zebrafish (Danio rerio), which include Grb10a and Grb10b. Characterization and expression studies for Grb10b gene location from the few major organs (eyes, brain, gills, stomach, intestine, liver, heart, skin, muscle, bone) in Zebrafish were carried out by construction of cDNA from its RNA and performing RT-PCR using a pair of primer consisting of forward primer (5’-gACCTgTgCCAgTTTCTCgT-3’) and reverse primer (5’-ATTCATACgCTgCTggCTTT-3’). RT-PCR amplification showed three organs with the correct product size, which is approximately 800bp. Thus, the expression study was partially successful and showed that Grb10b is a duplicated gene.